1994
DOI: 10.1007/bf02361247
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose intraperitoneal aprotinin treatment of acute severe pancreatitis: A double-blind randomized multi-center trial

Abstract: A multi-center double-blind trial was performed on 48 patients with severe acute pancreatitis. All patients were treated with intraperitoneal lavage. One group (n = 22) was also treated with high doses of the protease inhibitor, aprotinin (Trasylol; Bayer AG, Leverkusen, Germany) administered intraperitoneally. Eight patients died, giving a total mortality of 16.6%. No difference was observed between the two groups. Altogether, 12 patients were operated on, corresponding to 25%. In the group not treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…It has been hypothesised that administration of potential therapies by continuous regional arterial infusion or the intraperitoneal route may be advantageous. So far, trials using these modes of administration have only been in studies incorporating small numbers of patients [38] or of poor study design.…”
Section: Protease Inhibitors In Anpmentioning
confidence: 99%
“…It has been hypothesised that administration of potential therapies by continuous regional arterial infusion or the intraperitoneal route may be advantageous. So far, trials using these modes of administration have only been in studies incorporating small numbers of patients [38] or of poor study design.…”
Section: Protease Inhibitors In Anpmentioning
confidence: 99%
“…However, these findings could not be confirmed in subsequent studies [40,41] including a double-blind, randomized trial where aprotinin was given in relatively high doses for 5 days and no changes were found in the rate of recovery or incidence of complications [42]. When aprotinin was given though peritoneal lavage every 2 h to SAP patients, less pancreas necrosis, lower complement activation, and the acute phase response were reported although no significant decrease in mortality [43][44][45]. New protease inhibitors including gabexate mesylate (FOY), nafamostat mesilate and ulinastatin were developed in Japan in the 1970-1980s and harbor broader spectrum of inhibitory activities to many proteases.…”
Section: Intravenous Administration Of Protease Inhibitorsmentioning
confidence: 67%
“…A bibliographical research of the available literature also demonstrated the lack of a rationale in the pharmacological treatment of acute pancreatitis with somatostatin and octeotride 9-13 , protease inhibitors [14][15] , inhibitors of pancreatic secretion such as cimetidine, atropine, calcitonin, glucagon or fluorouracil. In fact, no evidence exists about the efficacy of these therapies in terms of mortality or complications.…”
Section: Discussionmentioning
confidence: 96%